Draft Genome Sequence of Exopolysaccharide-Producing Thermophilic Bacterium Brevibacillus thermoruber Strain 423 - (:unkn) unknown (My University, 2013)
Brevibacillus thermoruber strain 423 is a Gram-positive, spore-forming, aerobic, and thermophilic bacterium that produces mannogalactoglucan exopolysaccharide (EPS). We report the draft genome sequence of B. thermoruber 423, which will accelerate research on the cellular organization of thermophilic bacteria, as well as the rational design and optimization of EPS production.